Ricardo Palma: the great writer and young people of 900 - Gonzales Alvarado, Osmar (2019)
In this article, the author analyzes the intellectual work of Ricardo Palma, identifying him as an intellectual figure that embodies the great representative Peruvian writer. From that location, he describes the relationship he had with different members of the Nine hundred generation, who recognized him as theirmaster and incarnation of the national soul. For this, the author uses firsthand sources, such as personal letters, and known bibliography.